SAKLAR SUARA MENGGUNAKAN ARDUINO BERBASIS ANDROID - Rusli H; Sulaeman; Juniarti Iryani; muhammad awal nur (LPPM STMIK BINA ADINATA, 2021)
The research aims to: (1) produce a tool that can control the lighting of the lights at home using Android through human voice. (2) Implement a sound switch using an Android-basedArduino.The research method we use in making sound switch tool using Android-based Arduino is Action research method (Action Research) that attempts to try to get ideas into Prektik to fix or change something for real impact. As for Action research measures (Action Research): (1) plan; (2) Action; (3) Observation; (4) reflection;. The Technical data collection (1) observation; (2) interviews; (3) Library study.The results showed that (1) This tool can be turned on/off when user gives command via Android